We use the kinematic equation,
[tex]v^{2} = u^{2} +2gh[/tex]
Here, u is initial velocity, and v is final velocity, g is acceleration due to gravity and h is maximum height.
The velocity of the astronaut reaching the ground from h is
[tex]v=\sqrt{2 g_{earth} \times h_{earth} }[/tex]
Here, u = 0.
Similarly, for moon
[tex]v=\sqrt{2 g_{moon} \times h_{moon} }[/tex].
Take, [tex]g_{earth} = 9.8 m/s^2[/tex] and [tex]g_{moon} = 1.625 \ m/s^2[/tex].
For safe jump to the ground, the velocity should be same.
Therefore,
[tex]\sqrt{2 g_{earth} \times h_{earth} } = \sqrt{2 g_{moon} \times h_{moon} } \\\\
[tex]9.8 m/s^2 \times 1.2 \ m = 1.625 m/s^2 \times h_{moon} \\\\ h_{moon} = \frac{11.76}{1.625} = 7.2 \ m[/tex]
Thus, the astronaut safely jump to the ground on the moon from height 7.2 m.